IMPROVING WORK POSTURE TO REDUCE WORK RISKS: CASE STUDY IN A CRACKERS FACTORY - Kartika, Milana; Dewa, Parama Kartika; Afiah, Irma Nur (Journal of Industrial Engineering Management, 2024)
Culinary products in Yogyakarta include products that have a high level of demand. One of the products that consumers like is cracker. The process of making crackers in Yogyakarta is still predominantly done manually. This condition causes humans to play an important role in meeting cracker production targets. Based on observations and interviews with stakeholders in this cracker business, there are fundamental problems that must be resolved immediately. The problem is the number of complaints from production employees related to physical discomfort while working. This can lead to productivity issues. The expected solution is how to reduce the number of complaints of such employees.An ergonomic approach is used to solve this problem. Employee complaints regarding work discomfort are influenced by work risks present at production workstations. So that when work risks can be reduced, the number of employee complaints will also decrease. The method for assessing work risks and efforts to improve them is used the REBA method.Based on the priority of problems determined using the REBA method, information was obtained that the cracker printing workstation needs to be repaired immediately in order to reduce work risks. Improvements are made by designing trolley aids that can reduce the level of risk from a value of ten to five.